As relações sociais na contemporaneidade: os usos e apropriações do Facebook por alunos de uma universidade privada da cidade de Toledo-PR - Koch, Marilena Olga (2018)
The present study sought to find out how internet connectivity and interactivity via Facebook reveal characteristics of the connected contemporary subject. More specifically, the students' practices and the social relations established by them were analyzed and described. The exploratory research was carried out through case studies with eight students from a private university in the city of Toledo-PR. We sought to understand how these individuals are expressed and represented, who their interlocutors are and what practices these individuals develop in the social media. Through the observation of students' personal pages and in-depth interviews with them, it was found that Facebook, besides a space for interaction among users, is characterized as a locus of identity expressions of individuals.